Cardiac Autonomic and Cardiac Vagal Control During and After Depressive and Happiness Autobiographical Memories in Patients With Major Depressive Disorder - Lin, I-Mei; Wu, Yin-Chen; Su, Wen-So; Ke, Chiao-Li Khale; Lin, Pei-Yun; Huang, Mei-Feng; Yeh, Yi-Chun; Wu, Kuan-Ta; Yen, Cheng-Fang; Ko, Chih-Hung; Fan, Sheng-Yu (Frontiers in Psychiatry, 2022)
Background: Heart rate variability (HRV) and respiratory sinus arrhythmia (RSA) are indices of cardiac autonomic and cardiac vagal control (CVC), both of which are markers of emotional regulation and physical health. This study examined (1) the differences in cardiac autonomic regulation and CVC during baseline, depressive, and happiness autobiographical memory tasks between participants with major depressive disorder (MDD group) and healthy controls (HC group); (2) the associations between depressive symptoms and cardiac autonomic and CVC; and (3) the reactivity and recovery of cardiac autonomic and CVC between the MDD and HC groups. Methods: A total of 168 and 178 participants were included in the MDD and HC groups, respectively. Demographic data and Beck Depression Inventory-II were collected before the experimental procedure. Lead II electrocardiograph (ECG) was measured during baseline, depressive, and happiness autobiographical memory tasks, and then interbeat intervals from ECG were converted to time and frequency domains of HRV and RSA. Results: The participants in the MDD group showed lower HRV (including standard deviation of normal to normal intervals, low frequency, natural logarithm of low frequency, and natural logarithm of high frequency) and CVC (RSA and lnRSA) than those in the HC group. Depressive symptoms were positively correlated with heart rate and negatively correlated with the indices of cardiac autonomic and CVC. There was significantly increased reactivity and recovery of cardiac autonomic and CVC during and after depressive and happiness autobiographical memory tasks in the HC group, but not in the MDD group. Discussion: Participants with MDD had cardiac autonomic and CVC dysregulation, decreased reactivity, and did not recover to baseline after emotional provocations. These results can be the theoretical basis for clinical intervention by using HRV biofeedback to restore cardiac autonomic regulation and CVC during and after emotional events in the future.